Dynamic analysis for cracked fiber-metal laminated beams carrying moving loads and its application for wavelet based crack detection - Tao, Chang; Fu, Yiming; Dai, Ting (Composite structures, 2017)
The present study considered the free and forced vibration of cracked fiber metal laminated (FML) beams with a damper subjected to a moving load, and the detection of the cracks by using continuous wavelet transform (CWT). The beam is regarded as multi segments which are assumed to obey the Euler-Bernoulli beam hypothesis and the crack is modeled as rotational spring with sectional flexibility. The modal expansion theory and Newmark method are employed to solve the dynamic responses of FML beam numerically. Two classes of boundary conditions are considered and the dynamic responses at the tip of a FML cantilever beam with a single crack are obtained for various load velocity, and the outcome results have been compared to the results obtained by literature. The influences of crack depth, crack location, ply angle of the fiber layer, stiffness coefficient of the damper and velocity of the moving load on free vibration and forced vibration of FML cantilever beams are investigated. Numerical results indicate that the above-mentioned effects play a very important role on both free vibration and dynamic responses of the beam. In the end of the numerical examples, continuous wavelet transform is used to detect the location of the cracks of a clamped-clamped FML beam.